What premiums do target shareholders expect? Explaining negative returns upon offer announcements - Ang, James S.; Ismail, Ahmad K. (Journal of Corporate Finance, 2015)
We find, in a sample of 7581 merger offer announcements from 1990 to 2013, shareholders of 1283 (or 17%) target firms responded to the offer with negative market returns. These investors were disappointed at the offer, despite the price premium. To explain their disappointment, one must understand how target shareholders form expectations of premium to be received. We use a novel empirical design to find the relative weights of the rational vs. behavioral factors underlying the process of expectation formation. The estimated expected premiums are shown to have predictive power in the subsamples of both the positive and negative market responses. We also compare how the weights of the expectation factors change under different market conditions: hot vs. cold M&A regimes, bull vs. bear stock market, financial crisis vs. non-crisis periods, and dotcom bubble vs. no bubble.